QUNUT DALAM PERSPEKTIF HADIS - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Qunut in prayer is a problem that is furuiyyah in worship that comes from the proposition zdanniy. Asbab wurud its qunut is when the Prophet. heard the Prophet sent 70 people to help the tribe of Bani Salim, the tribes were massacred by the middle of the trip. This event is known as al-qurra events So that's when the Messenger of Allah. do qunut every dawn prayer as deep condolences and pray at the same time and melaksanat tribes have been treason. After a month he qunut, come down verse 128 Surah Ali Imran (3) a ban on praying for destruction, evil and curse others. After the verses came, the Prophet stopped within the meaning of praying for the destruction of others, but the Prophet remained qunut in prayer as described in Anas bin Malik narrated by Imam Bukhari. The tradition of Imam al-Baehaqi in his book al-Sunnah Kubra explains that qunut are not mengandungan prayer destruction, evil and curse others are still performed by the Prophet at dawn prayer.